Factors Associated with Parents' Belief in the Appropriateness of Providing Alcohol to their Child - Jongenelis, Michelle; Johnston, Robyn; Stafford, J. (Informa Healthcare, 2018)
© 2018 Taylor & Francis Group, LLC Background: Parental provision of alcohol to their underage child has been associated with risky adolescent drinking. While parents' belief in the appropriateness of providing their child with alcohol may influence their provision behaviors, research into the factors associated with this belief is lacking. Objectives: This study sought to identify the factors associated with parents' belief in the appropriateness of providing alcohol to their underage child. Methods: Western Australian parents of 12–17 year olds (n = 443) completed an online survey assessing their drinking habits, alcohol provision behaviors, alcohol-related beliefs and attitudes, their child's alcohol consumption, and demographics. Results: Nearly half (44%) the parents surveyed reported providing their underage child with alcohol. Parents of older children and parents who (i) did not believe in the harms and recommendations associated with alcohol use in youth, (ii) agreed with youth-related drinking myths, and (iii) reported more occasions of alcohol consumption by their child were more likely to believe that it was appropriate to provide alcohol to their underage child. Those who believed providing alcohol to their underage child was appropriate were in turn more likely to provide alcohol. Conclusions: Interventions aiming to reduce parental provision of alcohol to children should focus on changing parents' beliefs that this is an appropriate harm minimization behavior. Belief change may be facilitated by the implementation of public education campaigns that increase parents' belief in the alcohol-related harms associated with youth drinking and debunk youth-related drinking myths.